Практична реалізація педагогічних умов готовності майбутнього вчителя початкової школи до інклюзії - Гудзь, Катерина; Gudz, Kateryna (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті розкрито суть та структуру практичної реалізації педагогічних умов готовності майбутнього вчителя початкової школи до інклюзії. Розглянуто основні завдання готовності майбутнього вчителя початкової школи до умов інклюзивного навчання. Розроблено та обґрунтовано практичну реалізацію педагогічних умов формування культури спілкування майбутніх вчителів початкової школи в навчально-виховному процесі. The article examines the essence and structure of the practical implementation of pedagogical conditions of the preparation of future elementary school teacher to inclusion. We examined the main tasks of the readiness of future elementary school teacher to conditions of inclusive education. Also we have developed and proved the practical implementation of pedagogical conditions of formation communicative culture in future elementary school teacher in the educational process. Improving the readiness of the future elementary school teacher to the profession and to the introduction of personality-oriented technologies to form cognitive interest of junior pupils is one of the priorities in vocational and educational training to the conditions of inclusive education. The implementation of inclusion demonstrates the desire of our country to focus on international standards and human values in questions of establishing a system of assistance to people with special problems, provide equal rights and open up new opportunities. It`s very important that inclusion can eliminate any manifestation of social exclusion of children and adolescents with disabilities in psychophysical development. The starting point in practice and in self-education and self-improvement of the future teachers there are the content of their professional training to educational work and cooperation in the process of inclusive education along with the selection of appropriate teaching materials. We recognize the important components of personal and professional readiness of the future teacher which include the indissoluble unity of such components as motivational, cognitive, social and communicative, activity-technological, moral and aesthetic. Other important moments on which we pay our attention there are pedagogical communication in the educational process of elementary school and motivation in the preparation process of future elementary school teachers to pupil’s interaction in terms of inclusive education.
Practical Implementation of the Pedagogical Conditions of the Preparation of Future Elementary School Teacher to Inclusion
Keywords: інклюзія; інклюзивне навчання; професійна підготовка; готовність майбутнього вчителя; завдання готовності педагога; inclusion; professional training; inclusive education; the readiness of future teacher; the task of readiness of the teacher